Sámi Women. Terrestrial, Dialectal, Vigor, Ethos - Digioia, AK (2016)
Sámi women, much like other women of the world, have faced numerous attacks on their ancestral lands, language, health, and culture. Colonization, which spurs on institutions of colonization and oppression, can be seen as the ultimate form of violence against indigenous women. Indigenous women throughout the world share transnational injustices and patriarchal oppression, as patrilineal domination of indigenous women surpasses all boundaries.